Pelatihan Cyber Security Untuk Menjaga Keamanan Dan Privasi Siswa Smk Negeri 4 Banjarmasin - Yusup Indra Wijaya; Muhammad Saidi Rahman; Herry Adi Chandra; Muharir Muharir; Muhammad Amin (Universitas Kristen Indonesia Toraja, 2023)
Cybersecurity (or cyber security) is a series of efforts made to protect computer systems or digital networks from cyber attacks or unauthorized access. Threats to cyber security include virus attacks, phishing, denial-of-service (DDoS), hacking, and unauthorized access. Cyber ​​security is critical as more and more organizations and individuals rely on information technology in their operations. Cyber ​​security includes network security, application security, data security, identity security, and physical security. Cyber ​​security efforts involve identifying, preventing, responding to, and recovering from cyber attacks. The more complex cyber threats become, the more important it is to improve cyber security and protect systems from damage or data theft.